2008
DOI: 10.1186/1471-2474-9-170
|View full text |Cite
|
Sign up to set email alerts
|

Movement control tests of the low back; evaluation of the difference between patients with low back pain and healthy controls

Abstract: Background: To determine whether there is a difference between patients with low back pain and healthy controls in a test battery score for movement control of the lumbar spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
4
27

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(175 citation statements)
references
References 30 publications
8
136
4
27
Order By: Relevance
“…19,29,31 Previous assessments of dissociation of lumbopelvic from thoracic motion have involved dichotomous outcomes as a part of a test battery. 18 The present study is the first to assess the validity of a clinician's ability to evaluate thoracolumbar dissociation in participants with and without LBP and to use nondichotomous outcomes to allow greater scope to identify differences between, and changes within, individuals.…”
Section: Discussionmentioning
confidence: 99%
“…19,29,31 Previous assessments of dissociation of lumbopelvic from thoracic motion have involved dichotomous outcomes as a part of a test battery. 18 The present study is the first to assess the validity of a clinician's ability to evaluate thoracolumbar dissociation in participants with and without LBP and to use nondichotomous outcomes to allow greater scope to identify differences between, and changes within, individuals.…”
Section: Discussionmentioning
confidence: 99%
“…They found that experienced physiotherapists had difficulty in determining the status of patients by movement analysis alone (Hickey et al, 2007). In contrast, Luomajoki et al (2008) found significant differences between patients with and without low back pain in their ability to actively control movement of the low back. A study by Della Casa et al (2014) showed that a head-eye movement control test battery could discriminate between patients with chronic neck pain and healthy controls.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, knee extension in the sitting position is often used to classify low back pain in the movement control test 6,7) . Patients with hamstring shortness can exhibit compensatory lumbopelvic motions when performing knee extension exercises due to their shortened or stiff hamstrings, and this can be prevented if the exercise is performed correctly 2,8) .…”
Section: Introductionmentioning
confidence: 99%